Evaluation of slip behavior of self-locking modular steel connection - Nadeem, Gohar; Safiee, Nor Azizi; Abu Bakar, Nabilah; Abd Karim, Izian; Mohd Nasir, Noor Azline (Elsevier, 2022)
Modular steel building (MSB) is an exceptional substitute for traditional on-site steel construction. Bolt hole tolerance is provided in inter-modular connections (IMC) to allow positioning of modules which causes a higher initial slip of bolted connection. This study proposes a new connection with a four-stage assembly procedure that omits the need for excess hole tolerance in bolted connections and provides higher initial stiffness. The performance of this proposed connection is evaluated using finite element analysis, which has been validated against the existing experimental data from the literature. An analytical study is conducted on two variants of the proposed connection, the first variant with bolts and the second variant with dowel pins, to evaluate the shear force-slip behaviour. The force-displacement curve of the proposed connection is compared with existing models of bolted connections. Results show that the connections with pretension force applied on bolts had good agreement with the traditional four-stage model for bolted connection. Equations provided by established design codes can predict the initial stiffness in IMCs.